Recruitment challenges in MRI studies of acute intracerebral haemorrhage: experience from the TICH-2 MRI substudy - Pszczolkowski, Stefan; Bath, Philip M.W.; Sprigg, Nikola; Dineen, Robert A. (2018)
BACKGROUND AND AIMS Magnetic Resonance Imaging (MRI) is widely used in clinical practice and in trials for ischaemic stroke; however, relatively few large multicentre trials for intracerebral haemorrhage have used MRI. We describe the main recruitment challenges faced in the TICH-2 MRI substudy, which is nested within TICH-2, a multi-centre randomised placebo-controlled trial of tranexamic acid in intracerebral haemorrhage (ISRCTN93732214). METHOD TICH-2 participants at recruiting centres were eligible for the substudy. Centres were asked to record, if applicable, the reason for non-recruitment. The recruitment window was day 2 to day 14 post-randomisation. RESULTS Figure 1 shows the distribution of reasons for non-recruitment (N=169). Clinical instability was the main reason for non-recruitment, accounting for 34.3% of the cases. The mean NIHSS scores (as per TICH-2 protocol) for unrecruited patients classified as clinically unstable were 19 (range 5-32,N=57), 21 (range 0-40,N=51) and 20 (range 1-38,N=37) for baseline, day 2 and day 7 post-randomisation, respectively. In contrast, for recruited patients (N=142) the mean scores were 10 (range 0-28,N=141), 8 (range 0-26,N=139) and 8 (range 0-31,N=132). Other important factors for non-recruitment include difficulty obtaining consent, patient refusal, claustrophobia and transfer to other hospitals. CONCLUSION Clinical instability in intracerebral haemorrhage poses a challenge for recruitment into MRI studies. This, and other factors, should be taken into consideration when designing clinical trials of intracerebral haemorrhage involving MRI.